2002
DOI: 10.1104/pp.006064
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Oligogalacturonide- and Auxin-Induced Extracellular Alkalinization and Growth Responses in Roots of Intact Cucumber Seedlings

Abstract: Oligogalacturonic acid (OGA) affects plant growth and development in an antagonistic manner to that of the auxin indole-3-acetic acid (IAA), the mechanism by which remains to be determined. This study describes the relationship between IAA and OGA activity in intact cucumber (Cucumis sativus) seedlings. Both OGA and IAA induced rapid and transient extracellular alkalinization; however, the characteristics of the OGA and IAA responses differed in their kinetics, magnitude, calcium dependence, and region of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…wall alkalinization and growth responses in cucumber (Cucumis sativus) roots, Spiro et al (2002) concluded that auxin-induced alkalinization is not sufficient to account for the mechanism by which auxin inhibits root growth.…”
Section: Oh and To Respond Tomentioning
confidence: 99%
“…wall alkalinization and growth responses in cucumber (Cucumis sativus) roots, Spiro et al (2002) concluded that auxin-induced alkalinization is not sufficient to account for the mechanism by which auxin inhibits root growth.…”
Section: Oh and To Respond Tomentioning
confidence: 99%
“…Oligogalacturonic acids (OGAs) are biologically active oligosaccharides produced by the hydrolysis of de-esterified pectins (Spiro et al, 2002). Both plant and pathogen cell walls are a source of the oligosaccharide fragments generated during plant-pathogen interactions through the enzymatic hydrolysis of polysaccharides (Côté and Hahn, 1994;John et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in tobacco, OGs inhibit the induction of the late auxin-responsive genes Nt114, rolB, and rolD (Mauro et al, 2002). In cucumber (Cucumis sativus) seedlings, OGs allow for a more rapid recovery of root growth in auxin-treated roots (Spiro et al, 2002). To date, the mechanism underlying the antagonistic effect of OGs on auxin-induced responses is not known.…”
mentioning
confidence: 99%